Development of Mystery Box Media "Taringbarua (Pull the Net of Building Space)" In Learning Mathematics for Elementary School Students - Tania Tania; Risnina Wafiqoh; Sisi Pitriyana; Zhansaya K. Markhmadov (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2025)
This study addresses the issue of inadequate use of learning tools among students, which leads to decreased interest, reduced focus, and limited understanding of the material. It is the goal of this study to create a media mystery box taringbarua (pull the net wake space) that is trustworthy, useful, and aware of how it might affect the mathematics learning of elementary school children. ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model is used in this type of work as part of the research and development (R&D) method. There were 44 fifth graders from SD Negeri in the south Bangka area who took part in the study. To get information, we used tests, surveys, and interviews. E The N-Gain score was used for quantitative analysis, while qualitative data were analyzed through thematic review. Findings from the validity acquisition of questionnaires from media and material specialists show that the language evaluation is 100% "very good," the media assessment is 97.61% "very good," and the material assessment is 94.44% "very good." The acquisition of student answer surveys, which include one-to-one trials (96.67% "excellent"), small group trials (98.33%"excellent"), and field trials (86.15% "excellent"), demonstrates the practicality of assessment. Based on the test findings, which showed an average N-Gain of 72.77 in the "high" category, it can be said that the mystery box taringbarua media can improve students' conceptual comprehension.